Analisis Resiko Kegagalan Sistem Logistik Pelabuhan dan Dampaknya terhadap Efisiensi Pengiriman Bar - Fikri, Adam (Jurnal Ilmiah Wahana Pendidikan, 2024)
ABSTRACT Purpose : The purpose of this paper is to analyze the risk of port logistics system failure and its impact on freight forwarding efficiency. The specific objectives of this paper are to (1) identify risk factors affecting the port logistics system; (2) evaluate the impact of these risks on the efficiency of goods delivery; and (3) formulate risk mitigation strategies to improve the performance of the port logistics system. Method : This research uses the literature study method to analyze the risk of port logistics system failure and its impact on the efficiency of shipping goods. Result : Analysis of the risk of port logistics system failure and its impact on the efficiency of goods delivery is an important step in efforts to improve logistics performance. By understanding and effectively managing risks, ports can minimize potential failures and ensure the smooth flow of goods. This will ultimately contribute to improved customer satisfaction and economic competitiveness.